Design and Implementation of Cloud-Based Information Systems for SMEs: Enhancing Efficiency and Scalability - Kamaruddin Kamaruddin; Akbar Iskandar; Muh Riyaldi Pratama; Ming-Chung Chang (Ceddi Journal of Information System and Technology (JST), 2025)
Small and Medium Enterprises (SMEs) play a critical role in economic growth and employment, yet their ability to remain competitive is often constrained by limited capital, fragmented information infrastructure, and uneven digital capabilities. In recent years, cloud-based information systems have been increasingly adopted as an alternative to conventional IT infrastructures, particularly due to their scalability, flexibility, and reduced upfront investment requirements. This study examines the design and implementation of cloud-based information systems in SMEs and evaluates their implications for operational efficiency and organizational scalability. Using a quantitative explanatory research design, data were collected from SMEs that have implemented cloud solutions and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that organizational readiness and security risk management are decisive factors shaping the effectiveness of cloud system implementation. SMEs with adequate preparedness and structured risk controls are more likely to achieve measurable improvements in process efficiency, data integration, and decision-making responsiveness. In addition, the findings highlight that modular and scalable system architectures allow SMEs to adjust operational capacity in line with market fluctuations while avoiding excessive infrastructure costs. By empirically linking system design choices with organizational and governance conditions, this study contributes an integrated framework to the literature on SME digital transformation. The results also provide practical guidance for managers and policymakers in formulating cloud adoption strategies that support long-term digital resilience.